Oral health approach in Cuba - Gispert Abreu, Estela de los Ángeles (2020)
Oral health requires priority; a great challenge is to reduce the high burden of disease morbidity, in that way it is valid to share lessons. The aim of this article is to expose experiences of the oral health approach in Cuba as a social good and human right. The article characterized the organization and institutionalization of an organized care practice within the single national health system with universal coverage and state funding. This paper referenced to national programs and actions, human resources training being the Integral General Stomatology an integrative discipline based on the health analysis. Also, the specialty favors the integrated action within the primary health care. The results showed advances. It is concluded that several factors may facilitate addressing oral health as a social good and human right in Cuba; however, its improvement has challenges.